Muslim Prayer (Salah), and Its Restorative Effect: Psychophysiological Explanation - Suseno, Bayu (Universitas Muhammadiyah Surakarta, 2024)
Stress is the most common problem experienced by people across ages and is associated with poor psychological and physical health. Stress is related to emotional and mental states that can be seen psychologically, namely relaxed and focused, also physiologically through the central nervous system (CNS) and autonomic nervous system (ANS), both sympathetic (SNS) and parasympathetic nervous systems (PNS). Salah, as obligatory Muslim worship, is a coping strategy beneficial for psychological and other aspects, such as physical and neurological health. Salah has a restorative effect, such as reducing mental fatigue and stress, as explained by attention restorative theory (ART) and stress restorative theory (SRT). Salah can reduce stress, psychologically and physiologically, indicated by an increment in PNS [nuHF of heart rate variability (HRV), galvanic skin responses (GSR), heart rate (HR), and blood pressure (BP) activity and a decrease in SNS (nuLF and LF/HF of HRV) also increase of alpha brainwave which part of the central nervous system (CNS). In terms of focus, concentration, and awareness, salah is perceived as giving the worshiper a better mental state. In addition, salah increases the gamma power, which is part of CNS and related to awareness. Interestingly, the relaxation effect of salah is higher in the prostration position; also, reciting the Holy Quran while doing salah has higher effects on focus and attention than mimic salah. Apart from the obligation of salah, the psychological and physiological benefits of salah should make a Muslim pray obediently, and the finding that reciting the Holy Quran ayah during salah and prostration has a higher effect shows that remembering Allah is vital.